PHRASEOLOGISM AS ORGANIZATION OF TEACHING PROCESS: ФРАЗЕОЛОГИЗМЫ КАК ОРГАНИЗАЦИЯ УЧЕБНОГО ПРОЦЕССА - Ш.Цолмон; Ц.Сэрээнэн (Acta Mongolica, 2013)
The basis of any popular Pedagogy is reflected on all forms of folktales and in the traditional phrases that have been passed on to generations to generations becoming as a “popular book” by providing moral, intellectual, labor, beauty, and physical education to teenagers and youth with expressive words and artistic descriptions. This article classifies phraseological expressions considering the cognitive and pedagogical importance; and develop the training process effectively by using them.